A study of construction waste material management in Malaysia : a contractor point of view - Hilmi Hakim, Bakri (2017)
Malaysia nowadays is develop at steady pace, because of that increasing in development in Malaysia is predictable. Because of the rapid development in construction industry, construction waste becomes a major problem for contractor and environment. This can be proving with newspaper clippings issued by the newspaper 'The Star'. Therefore, this study is to highlight contractor‟s perception on various construction waste materials and major environment concerns cause by this construction waste. Besides that, it is also to identify the problem that may arise by the waste product and analyses a suitable method to solve the problem that occurs by the construction waste. This research will cover peninsular area of Malaysia. This research also will focus on the construction waste material management by the respondent of contractor that has been selected and registered to CIDB. The questionnaires were prepared and hand out to the person involved in construction project. Data gathering carried out by doing literature review, applying a questionnaire survey and making related interviews through contractor. Based on the literature review, several problem causes by waste materials have been identify. These factors were then ranked on their relative importance, based on data from a questionnaire survey distributed to a wide range of professions in the industry. Data that collected from this study is analysis using SPSS software and Microsoft excels to determine influential factors contributing to construction waste management in Malaysia. Based on the analysis conducted, objectives can be achieved through the study finds that transportation costs, and a place for insect breeding gets a high average index. However the way to overcome the problem of construction waste that gets the highest average index is to manage areas to locate construction waste. In conclusion, to all objectives have been achieved, the factors that cause increasing of the construction waste can be identified, as well as the solution to help the contractor will also be explained in this research.